E-BUDGETING IMPLEMENTATION ON PUBLIC FINANCIAL TRANSPARENCY AND ACCOUNTABILITY AT THE COMMUNICATION AND INFORMATION DEPARTMENT OF PADANG CITY - Arianto, Arianto; Amanda, Audrey; Fadhilah, Aura; Nur Fadila Qomari, Fatia; Faizul Candra, Iqbal; Putri, Melani; Saputra, Boni (Jurnal Ilmu Administrasi Negara, 2024)
Digital transformation in the government sector has become an urgent necessity to achieve transparent and accountable financial governance, in line with increasing public demands for public information disclosure and the implementation of good governance principles. This study aims to comprehensively analyze the implementation of E-Budgeting systems in enhancing public financial transparency and accountability at the Communication and Information Department of Padang City, focusing on identifying implementation processes, evaluating the contributions to transparency, analyzing the effects on accountability, and identifying constraints along with management strategies. The research employs a qualitative approach with an instrumental case study design involving methodological triangulation through semi-structured in-depth interviews, participatory observation, and document analysis. Data analysis is conducted using Braun and Clarke's six-phase inductive thematic analysis. Findings demonstrate that the phased implementation of E-Budgeting, with comprehensive system integration, has successfully improved budgeting process efficiency from 2-3 weeks to 3-5 working days, provided real-time information access to stakeholders, and created digital audit trails that strengthen transparency and accountability. The research offers practical implications for local governments to adopt holistic implementation models in digitalizing financial management while contributing theoretically to the development of effective e-government implementation frameworks in developing countries.